21st Annual IEEE International Symposium on Personal, Indoor and Mobile Radio Communications 2010
DOI: 10.1109/pimrc.2010.5671966
|View full text |Cite
|
Sign up to set email alerts
|

Receiver design for downlink MIMO MC-CDMA in cognitive radio systems

Abstract: Multiuser interference (MUI) and co-space interference (CSI) are two challenging issues in design of multicarrier code-division multiple-access (MC-CDMA) systems when multiple antennas are used at both the transmitter and receiver sides (MIMO transmission). On the other hand, in cognitive radio (CR) system, the secondary users that use MC-MCDA technique must deactivate the subcarriers used by the primary users. This leads to loss of orthogonality of the conventional spreading codes such as Hadamard Walsh codes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…For this purpose, the complex orthogonal CI codes are deployed. When the orthogonal Hadamard–Walsh codes of the same length exist, it has been shown that the error performance of CI codes is the same as that of the Hadamard–Walsh codes . We call this scheme as NC‐CI.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this purpose, the complex orthogonal CI codes are deployed. When the orthogonal Hadamard–Walsh codes of the same length exist, it has been shown that the error performance of CI codes is the same as that of the Hadamard–Walsh codes . We call this scheme as NC‐CI.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The first challenge is the need for the set of spreading codes with any arbitrary length because the number of remaining data subcarriers would be any integer value. The most widely proposed solution is the utilization of complex carrier interferometry (CI) codes . The second challenge is the power leakage to the adjacent frequency bands licensed to primary system that is due to the unwanted large spectral sidelobes of the active subcarriers.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we have focused on developing a suitable MC‐CDMA based transmission scheme for the cognitive radio networks. In the literature, two different transmission modes are proposed for the MC‐CDMA based secondary networks: underlay and overlay . We have considered the overlay mode where the secondary MC‐CDMA network is allowed to use a certain bandwidth shared with the users of a primary system such that minimum interference is made on primary users (PUs).…”
Section: Introductionmentioning
confidence: 99%
“…First, this system requires a set of signature sequences (i.e., spreading codes) that exist with any optional length because the number of remained data bearing subcarriers located in the allowed part of the spectrum can be any integer value. The deployment of orthogonal complex carrier interferometry (CI) signature sequences is the most important solution proposed for this purpose . The second challenge is the intrinsic drawback of the Fourier based multicarrier techniques: power leakage because of the spectral sidelobes of the Fourier based MC implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Multicarrier code division multiple access (MC-CDMA) [1,2] is a promising solution for the physical layer of future multiuser wireless networks, such as 4G cellular networks [3,4], broadband wireless access [5], and cognitive radio systems [6,7], especially for the downlink transmission. With the combination of orthogonal frequency division multiplexing (OFDM) and CDMA, it benefits from the advantages of both techniques, in particular, high data rate transmission capability in multipath environments, flexibility in spectrum use, and large multiple access capacity.…”
Section: Introductionmentioning
confidence: 99%